Optimization Forward- Fly back converter using MATLAB - Patil, Vinodkumar P; Patil, Rahul M; Tavar, Tejveersingh (International Journal of Engineering and Management Research, 2025)
This study offers an examination of forward and flyback converters by emphasizing important performance metrics, including power factor, efficiency, offset current, and core loss. Each topology has benefits and disadvantages of its own. A comparative assessment of performance characteristics is carried out through conversation and observation to overcome these constraints. The results suggest that combining both topologies with suitable switching devices, such as MOSFETs with quick switching capabilities, may improve total performance. This paper also looks at a suggested merged forward-flyback converter architecture and shows how it could be used to make a single-stage system more efficient and improve its power factor.